Microfabric characteristics of potash ore of the Pripyat potash-bearing basin - Petrova, Natalia S.; Denisova, Natalia Yu.; Kirykovich, Aliaksei V. (Journal of the Belarusian State University. Geography and Geology, 2019)
The requirements of complex subsoil use are increasing in the Pripyat potash-bearing basin: potash ore of new technologic types, with lower contents of useful components, increased concentrations of harmful impurities. Using all complex of quality indicators assessment of natural types of potash ore is undoubtedly prioritized by characteristic of potash deposits. The study of structural and textural features and composition of potash deposits has been given attention since the time of discover of the Starobin deposit. Systematic study of salt rock petrology has been started after the discovery of the Starobin deposit. Until now in the petrology, there is no recognized rational genetic classification of the structures of salt rocks being potash (potassium-magnesium) ore. The name of certain structure is based on the secondary features that are brightly expressed, color or similarity with different objects. The aim of the present work is an element recognition of the primary sedimentary features of rocks, systematization of primary and secondary characteristics and their typification according to petrochemical parameters. In the article the main microfabric types of potash ore that are typical for the deposits of red-colored and mottled hypersaline association of the Pripyat basin.
Keywords: Pripyat trough; potash ore; potash horizon; Starobin deposit; Petrikov deposit; salt-bearing formation; microfabric